Robust constrained stabilization of boost DC–DC converters through bifurcation analysis. (February 2015) - Yfoulis, C.; Giaouris, D.; Stergiopoulos, F.; Ziogou, C.; Voutetakis, S.; Papadopoulou, S.
Abstract: This paper proposes a new methodology for designing robust affine state-feedback control laws, so that wide-range safe and efficient operation of switched-mode DC–DC boost converters is guaranteed. Several undesirable nonlinear phenomena such as unstable attractors and subharmonic oscillations are avoided through bifurcation analysis based on the bilinear averaged model of the converter. The control design procedure also relies on constrained stabilization principles and the generation of safety domains using piecewise linear Lyapunov functions, so that robustness to supply voltage and output load variations is ensured, while input saturation is avoided and additional state constraints are also respected. The technique has been numerically and experimentally validated. Abstract : Highlights: We combine constrained stabilization and bifurcation theory for DC–DC converters. We demonstrate that performance deterioration due to multiple equilibria is possible. A thorough investigation of the bifurcation phenomena is presented. We prove that the averaged model can unfold the core nonlinear system׳s behavior. A new control design procedure for boost DC–DC converters is proposed.